2016
DOI: 10.3390/s16111851
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Neural Recording and Electrochemical Performance of Microelectrode Arrays Modified by Rough-Surfaced AuPt Alloy Nanoparticles with Nanoporosity

Abstract: In order to reduce the impedance and improve in vivo neural recording performance of our developed Michigan type silicon electrodes, rough-surfaced AuPt alloy nanoparticles with nanoporosity were deposited on gold microelectrode sites through electro-co-deposition of Au-Pt-Cu alloy nanoparticles, followed by chemical dealloying Cu. The AuPt alloy nanoparticles modified gold microelectrode sites were characterized by scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS), cyclic voltam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 86 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…The targeted impedance range of microelectrodes is from ~0.1 to 2 M Ω with the proper recording system utilization (Neto et al, 2018 ). Although some studies indicate the impedance does not have a major impact on the signal quality (Arcot Desai et al, 2010 ), most studies state that electrochemical impedance greatly affects the signal recording quality (Chung et al, 2015 ; Kozai et al, 2015 ; Zhao et al, 2016 ). The design of electrodes present tradeoffs in dimensions, electrochemical impedance, and background noise of recording.…”
Section: Key Materials Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The targeted impedance range of microelectrodes is from ~0.1 to 2 M Ω with the proper recording system utilization (Neto et al, 2018 ). Although some studies indicate the impedance does not have a major impact on the signal quality (Arcot Desai et al, 2010 ), most studies state that electrochemical impedance greatly affects the signal recording quality (Chung et al, 2015 ; Kozai et al, 2015 ; Zhao et al, 2016 ). The design of electrodes present tradeoffs in dimensions, electrochemical impedance, and background noise of recording.…”
Section: Key Materials Characteristicsmentioning
confidence: 99%
“…Furthermore, alloys with two or more than two metals have been investigated for nanoparticle synthesis to improve the stability of metallic nanoparticles. One example is the bimetallic Au/Pt alloy nanoparticle modified Au microelectrode, which exhibits an average 1 kHz impedance of 0.23 M Ω with a recording site of 20 μm diameter (Zhao et al, 2016 ), as shown in Figure 3A .…”
Section: Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…How much does an electrode’s impedance affect its signal-to-noise ratio (SNR) and thus ability to detect spikes? Several studies suggest that electrode impedance has a major impact on SNR ( Ludwig et al, 2006 ; Keefer et al, 2008 ; Ferguson et al, 2009 ; Ansaldo et al, 2011 ; Baranauskas et al, 2011 ; Du et al, 2011 ; Ludwig et al, 2011 ; Scott et al, 2012 ; Chung et al, 2015 ; Kozai et al, 2015 ; Zhao et al, 2016 ). However, there is also literature showing that electrode impedance does not greatly affect SNR ( Cui et al, 2001 ; Suner et al, 2005 ; Desai et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effective surface area of electrodes can be calculated based on the CV diagram 47,49 . Based on the values of the correlation constant at a cyclic rate of 25–1000 mV/s, 0.0012 and 0.0014 (anodic and cathodic sweep) for Sputt electrodes and, 0.0025 and 0.0029 (anodic and cathodic sweep) for Rough-Sputt electrodes, the effective surface area of 78.2 mm 2 and 37.8 mm 2 for the Rough-Sputt and Sputt electrode has been calculated respectively.…”
Section: Resultsmentioning
confidence: 99%